Ich habe keine Zeit: Gegenargumente im Denken von Karl Barth und Luce Irigaray - Hennecke, Susanne (Proeven van vrouwenstudies theologie ; deel V, 1999)
In her contribution Susanne Hennecke demonstrates how the modern problem of lack of time ('I haven't got time') can fruitfully be approached by combining the insights of systematic theology with philosophy. She does this by bringing the thinking of Luce Irigaray in her work La croyance même into a theoretical dialogue with the section 'Die Zeit der Offenbarung' in Karl Barth's Kirchliche Dogmatik. The problem of not having time is connected by both thinkers with the problem of the development of human (female) subjectivity. In particular, both share the thesis that in contrast to an old era of inauthentic existence, a new age of authentic life has dawned. However Hennecke shows that whereas for Barth, Christ reveals the possibility of new life, for Irigaray the angels stand at the threshold of authentic existence. Is Irigaray intending to propose a new Christology with her theory or to offer an alternative to Christology?